1996
DOI: 10.1107/s0907444995013977
|View full text |Cite
|
Sign up to set email alerts
|

An Ambiguous Structure of a DNA 15-mer Thrombin Complex

Abstract: The structure of a complex between thrombin and a GGTTGGTGTGGTTGG DNA 15-mer has been analyzed crystallographically. The solution NMR structure of the 15-mer has two stacked G-quartets similar to that found in the previous X-ray structure determination of the 15-mer-thrombin complex [Padmanabhan, Padmanabhan, Ferrara, Sadler & Tulinsky (1993). J. Biol. Chem. 268, 17651-17654]; the strand polarity, however, is reversed from that of the crystallographic structure. The structure of the complex here has been redet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
198
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(210 citation statements)
references
References 29 publications
7
198
0
5
Order By: Relevance
“…Conceptual visualization of the aptamer based sensing platform with fluorescently labeled aptamers (TBA1 with green and TBA2 with red label) forming a sandwich with thrombin on patterned glass surfaces, i.e., spotted microarray (left) and microcontact printed array (right). Molecular structures for this scheme were taken from the RCSB protein data bank (PDB ID: 1HAO) 39 and visualized in VMD 1.9.1. the addition of succinic anhydride dissolved in DMSO (final concentration: 10 mg/mL) the amino surface was carboxylated in a ring-opening reaction. After 30 min, the samples were rinsed with DI water in an ultrasonic bath for 3 min and dried with N 2 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Conceptual visualization of the aptamer based sensing platform with fluorescently labeled aptamers (TBA1 with green and TBA2 with red label) forming a sandwich with thrombin on patterned glass surfaces, i.e., spotted microarray (left) and microcontact printed array (right). Molecular structures for this scheme were taken from the RCSB protein data bank (PDB ID: 1HAO) 39 and visualized in VMD 1.9.1. the addition of succinic anhydride dissolved in DMSO (final concentration: 10 mg/mL) the amino surface was carboxylated in a ring-opening reaction. After 30 min, the samples were rinsed with DI water in an ultrasonic bath for 3 min and dried with N 2 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The crystal structure of a DNA aptamer bound to thrombin was published in 1993 and 1996, and the structure provided the first example of how a DNA aptamer could interact with a protein that does not naturally recognize a nucleic acid (Bock et al 1992;Padmanabhan et al 1993;Padmanabhan and Tulinsky 1996) Moreover, mutagenesis studies on thrombin confirmed that the DNA aptamer binds exosite 1 (Padmanabhan et al 1993). Similar thrombin mutagenesis studies indicated that the RNA aptamer TOG25 binds to thrombin near exosite 2 (Jeter et al 2004).…”
Section: Dna and Rna Aptamers Bind To Thrombin On Different Exositesmentioning
confidence: 99%
“…In structures of aptamers bound to nucleic acid binding proteins, the aptamers bind to the nucleic acid binding site and often mimic naturally occurring interactions (Convery et al 1998;Jaeger et al 1998;Cox et al 2002;Huang et al 2003;Ghosh et al 2004). The crystal structure of a DNA aptamer bound to thrombin has been determined (Padmanabhan et al 1993;Padmanabhan and Tulinsky 1996). This is the only crystal structure so far determined of an aptamer in complex with a protein that does not naturally bind nucleic acid.…”
Section: Introductionmentioning
confidence: 99%